PROSES MASUK DAN PERKEMBANGAN AGAMA KRISTEN PROTESTAN DI SAGITSI-MENTAWAI 1901-1916 - Exlessia, Wenti; Nurhuda, Ahmad; Kharles, Kharles (Pendidikan Sejarah, 2014)
This research aims to change the nature, thought patterns and attitudes in society to the desired state is a success. This can be seen in the efforts of Protestant Christian missionaries who came in Sagitsi who has managed to instill Protestant Christianity, cultivate awareness of education, modern medicine, regulation and encourage a better life than before.The method in this study is the method of historical research. This method consists of four subjects namely, (1) Heuristics of data collection from primary and secondary sources, which is done with the interview through books and relevant thesis that has to do with the writing. (2) the source of the criticism is done after the data collected to see whether the data is relevant to this paper or not. (3) Interpretation of explaining the data that was obtained to proceed to the stage of writing. (4) Historiography which is the stage of history that shaped the writing of scientific papers or thesis.From this study it can be seen that the people who used to Sagitsi largely adheres to the belief Sabulungan Arat, since the arrival of the German Missionary work closely with the Hurrians zending Protestant (HKBP) pioneered by Ps. August A. Lett and colleagues Kraimer, then the people berelih embraced Protestant Christianity. Although people who embraced Protestant Christianity only a small part, this is a starting point for the development of Protestant Christianity in sagitsi which covers an area of Mara, Monga, Nem-Nem Leleu and Sioban.Â The conclusion of this study is that previous Protestant Christianity through a difficult process, has grown in Sagitsi. It can be seen from the increase in the area that was once only gospel Pengkabaran Sipora island then extends into four regions. The existence public attitudes that have spontaneously Â Sabulungan Arat, then embraced Protestant Christianity, and no longer feel afraid to curse the spirit Sabulungan because Almighty God that they worship is forgiving, pengasihi, and compassionate in accordance with the teachings taught in Religion Protestant.